2015
DOI: 10.1007/s00125-015-3822-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific inflammation induced by MCP-1 overexpression does not affect whole-body insulin sensitivity in mice

Abstract: Aims/hypothesisObesity is associated with a state of chronic low-grade inflammation that is believed to contribute to the development of skeletal muscle insulin resistance. However, the extent to which local and systemic elevation of cytokines, such as monocyte chemoattractant protein 1 (MCP-1), interferes with the action of insulin and promotes insulin resistance and glucose intolerance in muscle remains unclear. Here, we aim to investigate the effect of muscle-specific overexpression of MCP-1 on insulin sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…A muscle defect in the activation of the insulin meta bolic pathway (Akt phosphorylation) was identified as an early mechanism of insulin resistance development in these populations (Amouzou et al 2016). Along with the study by Amouzou et al, recent animal data has also suggested the existence of alternative mechanisms, independent of previously proposed skeletal muscle inflammation, to generate insulin resistance (Evers-van Gogh et al 2016; Rivas et al 2016). If we consider that skeletal muscle macrophages have a critical role in promoting muscle recovery and regeneration (Chazaud 2016), we might speculate that there could be an impaired ability to mediate muscle regeneration among obese individuals.…”
Section: Discussionmentioning
confidence: 78%
“…A muscle defect in the activation of the insulin meta bolic pathway (Akt phosphorylation) was identified as an early mechanism of insulin resistance development in these populations (Amouzou et al 2016). Along with the study by Amouzou et al, recent animal data has also suggested the existence of alternative mechanisms, independent of previously proposed skeletal muscle inflammation, to generate insulin resistance (Evers-van Gogh et al 2016; Rivas et al 2016). If we consider that skeletal muscle macrophages have a critical role in promoting muscle recovery and regeneration (Chazaud 2016), we might speculate that there could be an impaired ability to mediate muscle regeneration among obese individuals.…”
Section: Discussionmentioning
confidence: 78%
“…While a report shows that local inflammation induced by muscle MCP-1 overexpression interferes with insulin signaling in muscle [60], the other study does not report a similar observation [61]. The following signaling pathways are currently being examined for sarcopenic obesity and IR.…”
Section: At Skeletal Musclementioning
confidence: 96%
“…Therefore, chemokines secreted by myocytes or adipocytes may play crucial roles in immune cell infiltration and inflammation in SM and visceral AT. MCP-1 overexpression in myocytes or adipocytes increases inflammation with enhanced immune cell infiltration in SM or visceral AT in mice (37,76), while MCP-1 knockout prevents HFD-induced increases in muscle or AT macrophages (53). The RANTES/CCR5 pathway is also upregulated in SM and visceral AT in obesity (9,35,77) and may play a role in obesity-linked inflammation in visceral AT (77).…”
Section: Skeletal Muscle Inflammation and Insulin Resistance In Obesitymentioning
confidence: 99%